Implementation of Make a Match Cooperative Learning Model to Improve Understanding of the Pillars of Islam in Grade 2 Elementary School Students - Anita Yuliyati (Journal of Islamic Pedagogy and Educational Development, 2025)
Background: This research is motivated by the low understanding of grade 2 elementary school students on the material of the Pillars of Islam which is indicated by only 40% of students achieving the KKM. The purpose of this study is to improve understanding of the Pillars of Islam through the implementation of the make a match cooperative learning model. Method: This research is a Classroom Action Research (CAR) which is carried out in two cycles with research subjects of 25 grade 2 students of Elementary School 59 Bengkulu City. Data collection techniques use observation, tests, documentation, and field notes. Results: The results of the study showed an increase in student understanding from the pre-cycle by 40% (average 65.2), increasing in cycle I to 64% (average 72.8), and in cycle II reaching 84% (average 82.4). Student activity also increased from 65% in cycle I to 85% in cycle II, while teacher skills increased from 75% to 88%. Conclusion: In conclusion, the application of the cooperative learning model of the make a match type can improve the understanding of the Pillars of Islam in grade 2 elementary school students.